Long-Term Medical Resource Consumption of Radical Prostatectomy vs. Intensity-Modulated Radiotherapy for Old Patients With Prostate Cancer: A Nationwide Population-Based Cohort Study - Wu, Szu-Yuan; Effendi, Fransisca Fortunata; Peng, Jhao Yang; Huang, Chung-Chien (Frontiers in Medicine, 2022)
PURPOSE: Few studies have compared the long-term medical resource consumption between radical prostatectomy (RP) and intensity-modulated radiation therapy (IMRT) among old (≥80 years) patients with localized prostate cancer (LPC), particularly in those at high risk of prostate adenocarcinoma. PATIENTS AND METHODS: The propensity score matching was conducted to investigate the medical expenditure of two therapeutic modalities (RP and IMRT) in elderly patients with high-risk LPC (HR-LPC). The generalized linear mixed and logistic regression models were employed to evaluate the number of postdischarge visits and medical reimbursement for urinary diseases or complications and the number of hospitalizations for treatment-related complications over 5 years after treatment, respectively. RESULTS: Significant differences were observed in the median or mean urology clinic visit numbers across the two therapeutic modalities from the first until fifth year post treatment (p < 0.0001). After adjustment for covariates, the mean difference (95% confidence interval [CI]) of urology clinic visit numbers between RP and IMRT was 13.07 (10.45–15.49, P<0.0001 ), 7.47 (8.01–14.92, P<0.0001), 8.24 (4.59–9.90, P<0.0001), 6.63 (3.55–11.70, P<0.0001), and 5.02 (1.12–8.73, P<0.0001) for the first, second, third, fourth, and fifth years, respectively. In the logistic regression multivariate model with adjustment for covariates (therapy type, age, diagnosis year, income, hospital area, hospital level [academic or nonacademic], clinical and pathological T-stage, grade [Gleason score], pretreatment PSA level [ng/mL], and D’Amico risk classification), the adjusted odds ratio (95% CI) of IMRT was 2.10 (1.37–2.56, P=0.0013), 1.55 (1.08–2.21, P=0.0151), 1.35 (1.08–2.21, P=0.0084), 1.24 (1.07–2.21, P=0.0071), and 1.09 (1.02–1.81, P=0.0379) for the first, second, third, fourth, and fifth years, respectively, compared with those of RP. The mean difference (95% CI) of total medical claims amounts of RP and IMRT between the RP and IMRT + ADT groups was 2,69,823 New Taiwan Dollars (NTD) (2,47,676–2,91,970, P<0.0001), 40,803 NTD (17,379–54,228, P<0.0001), 36,202 NTD (24,375–68,029, P<0.0001), 26,708 NTD (11,179–54,595, P=0.0321), and 12,173 NTD (17,140–41,487, P=0.0187) for the first, second, third, fourth, and fifth years, respectively. CONCLUSION: The long-term medical resource consumption was higher in old men with HR-LPC undergoing IMRT than in those undergoing RP.